(untitled) (Marketing Journal, 2025)
This article analyzes the digital transformation of the "Mahalla Yettiligi" (Mahalla Seven) system and its social significance. The integration of modern information and communication technologies (ICT) into local governance systems is a crucial factor in enhancing administrative efficiency, ensuring transparency, and promoting interactive communication with citizens. Global experience shows that digitalized mahalla systems enable the prompt identification of community issues and provide services in a transparent and efficient manner. The article evaluates the “Mahalla Yettiligi” system based on Uzbekistanʼs experience and international practices using the DESI (Digital Economy and Society Index) model. The findings indicate that the system currently has a 58% readiness level, requiring full integration and further development. Moreover, strategies are proposed for improving digital infrastructure, expanding e-government services, increasing ICT literacy, and utilizing artificial intelligence and Big Data technologies. This study presents a scientific approach to exploring the transition of mahallas to smart governance systems and improving local administration through modern digital solutions.